Improving Fifth Grade Student Learning Outcomes through Science Learning at MIS Nurul Yaqin - Nurfisah Nurfisah; Tabroni Tabroni; Heroza Firdaus (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to improve students’ learning outcomes in the subject of Natural and Social Sciences (IPAS) through the implementation of the Problem Based Instruction (PBI) model in class V-C at MIS Nurul Yaqin Muaro Jambi. The research method used was Classroom Action Research (CAR), conducted in two cycles with 22 students as the research subjects. Data collection techniques included observation, interviews, learning outcome tests, and documentation. The data were analyzed using qualitative and quantitative descriptive methods. The results showed that the implementation of the PBI model increased student engagement, improved the learning process, and significantly enhanced learning outcomes. This was indicated by an increase in learning mastery from 40.90% in the initial condition to 77.27% in Cycle I and further to 90.91% in Cycle II. Therefore, it can be concluded that the Problem Based Instruction model is effective in improving students’ learning outcomes in IPAS, particularly on the topic of Earth as a Living Space.